Ileocolic Atresia due to Internal Herniation through the Falciform Ligament Defect - Jiledar Rawat; Sudhir Singh; Gurmeet Singh (EL-Med-Pub, 2018)
Ileocolic atresia is the rarest form of all gastrointestinal atresia. Most accepted theory for Ileocolic atresia is a sequel of in-utero vascular insult. The incidence of internal hernia through a defect in the falciform ligament is extremely rare. In this case, a 2-day-old newborn baby presented with intestinal obstruction. On exploratory laparotomy ileocolic atresia was found along with the atretic terminal ileum and cecum, ascending colon and part of right transverse colon seen herniating through the defect in falciform ligament. To best of our knowledge and literature search this is the first case of Ileocolic atresia caused by intrauterine internal herniation of ileocolic segment through the falciform ligament defect.